2020
DOI: 10.1016/j.scitotenv.2020.139765
|View full text |Cite
|
Sign up to set email alerts
|

Increased ozone levels during the COVID-19 lockdown: Analysis for the city of Rio de Janeiro, Brazil

Abstract: Primary atmospheric pollutant concentrations decreased during the lockdown. • Ozone levels increased during lockdown in many cities of the world. • Ozone levels were related to the increase in NMHC/NO x ratios in a VOCcontrolled scenario. • Air masses from the industrial areas contributed to ozone increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
138
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 19 publications
22
138
0
14
Order By: Relevance
“…Similar to the present study reduction in PM10, PM2.5, NO2, CO and SO2 levels and a significant enhancement in O3 is observed at Iran, China, Kazakhstan, Singapore, Morocco, Brazil, Malaysia and Spain (Table 2) (Broomandi et al, 2020;Chen et al, 2020;Kerimray et al, 2020;Li and Tartarini, 2020;Otmani et al, 2020;Siciliano et al, 2020;Suhaimi et al, 2020;Tobias et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Similar to the present study reduction in PM10, PM2.5, NO2, CO and SO2 levels and a significant enhancement in O3 is observed at Iran, China, Kazakhstan, Singapore, Morocco, Brazil, Malaysia and Spain (Table 2) (Broomandi et al, 2020;Chen et al, 2020;Kerimray et al, 2020;Li and Tartarini, 2020;Otmani et al, 2020;Siciliano et al, 2020;Suhaimi et al, 2020;Tobias et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Ozone in 2020 was found to have higher values than the historical mean. Similar trends, attributed to a decrease in nitrogen oxide concentration, have been observed in Brazil (Siciliano et al 2020), Barcelona (Tobías et al 2020), and India (Mahato et al 2020;Sharma et al 2020a). The greatest effect of lockdown on air pollution could be observed in NO 2 distribution over Port Harcourt.…”
Section: Resultssupporting
confidence: 74%
“…Similar findings are reported in Thailand ( Stratoulias and Nuthammachot, 2020 ), China and Japan ( Ma and Kang, 2020 ; Zhang et al, 2020 ), Ecuador ( Zalakeviciute et al, 2020 ), Iran ( Broomandi et al, 2020 ), Milan, Italy ( Collivignarelli et al, 2020 ) and Morocco ( Otmani et al, 2020 ). Siciliano et al (2020) and Zhao et al (2020) , in turn, identified noteworthy increases in ozone concentrations (O 3 ) during the measures of social distancing adopted respectively by Brazil and China.…”
Section: Resultsmentioning
confidence: 98%